Interlanguage in writing ability of early semester students of IBIT Denpasar - Gede Eka Wahyu; Ketut Artawa; Ni Made Dhanawaty (Politeknik Negeri Bali, 2019)
The purpose of the study is aiming to discover the interlanguage system produce by students in writing an English composition. There were 25 descriptive text compositions as an instrument used to obtain the data. Qualitative research is administered in the study. Descriptive qualitative is used to evaluate and present data. The result of the study shows that most of students error in English writing are omission (-s) as plural form 25 %, then, 6,2 % error in using of the article, there were 5,7 % error in the use of verb have and preposition. Surface structure taxonomy proposed by Carl James is administered to analyzing data. Type of error found in the student composition was an error in omission, addition, misformation, misordering and blend.